Inquiry into phenomenology of mystical experiences: a defense of the perceptual model - Ksenija Puškarić (Nova Prisutnost, 2025)
This paper explores the phenomenology of mystical experiences and its philosophical implications. The focus will be on defending Alston’s view that there are perceptual kinds of mystical experiences, a view that has been historically prominent. In Christian mystical tradition the most influential discussions on spiritual senses were led by Origen and respected theologians like Karl Rahner and Hans Urs von Balthasar. The question of phenomenal qualities of such experiences will be discussed, as well as the role of emotions in mystical cognition. In addressing the problem of inter-subjective confirmation and articulation of such largely ineffable experiences, it will be argued that analytical methods are limited, but this is not philosophically problematic. The conclusion affirms the thesis that mystical experiences of the holy and infinite resemble sensory perception in its essential features.